AN EFFORT TO PREVENT INCORRET PLN’S INVOICE FOR REGULAR CUSTOMERSHOUSING PURPOSE IN PALANGKA RAYA - Wiratno (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
This research conducted for discover caused factor of the incorrect invoice of PLN electric power consumption and any effort to minimize its incorrect invoice. The research was conducting at ten (10) random houses in Palangka Raya as its sample. All researched houses had inconvenience experience with PLN invoicing. The PLN clerks were complaining against access to records compsumtion gauge. It problem raised due to PLN terminal was fitting far away from the house bound. Its condition has been quite making bit difficult for PLN clerks to see visually. Its current situation expected to be improved by re-fitting the gauge to lookable, but safe. A full suppots of regular customers also be expected.